Empowering the new mobility workforce : educating, training, and inspiring future transportation professionals - Reeb, Tyler (Elsevier, 2019)
Empowering the New Mobility Workforce: Educating, Training, and Inspiring Future Transportation Professionals enlists a multidisciplinary roster of subject matter specialists who identify the priorities and strategies for cultivating a skilled workforce for the rapidly changing transportation landscape. Transportation employers will need to hire 4.6 million workers--1.2 times the current transportation workforce--in the next decade. The book explores how leaders in education, industry and government can work together to create an ecosystem that facilitates learning and upskilling for emerging and incumbent transportation workers. Readers will learn how to conduct labor market analyses and develop competency models to adapt their workforce. This book will empower readers to establish ongoing communities of practice that cultivate sustainable career pathways that respond to ever-evolving socioeconomic trends and transformational technologies. Provides a comprehensive assessment of the new technologies and consumer attitudes driving change in personal vehicle, mass transit, active transportation, and goods movement, both domestically and internationally; Identifies the career pathways, experiential learning models, and types of curriculum needed to prepare emerging professionals to develop and operate transportation systems of the future; Emphasizes, through case studies, innovative practices emerging in public- and private-sector transportation organizations; Draws on key work conducted in the United States and around the world, acknowledging the increasing interconnectedness of transportation systems between countries, economies and social networks that transcend national boundaries.